2020
DOI: 10.1521/soco.2020.38.1.40
|View full text |Cite
|
Sign up to set email alerts
|

How Attribution-of-Competence and Scale-Granularity Explain the Anchor Precision Effect in Negotiations and Estimations

Abstract: Precise numbers are more potent anchors than round ones. Two theoretical mechanisms have been suggested to account for this anchor precision effect: (1) the scale-granularity account postulates that individuals adjust away from the anchor in smaller steps on a finer-grained mental scale, and (2) the attribution-of-competence account postulates that people ascribe more competence to a precise-opening individual. Direct empirical evidence for both accounts is scarce, however, and exists mainly for the attributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 36 publications
1
29
2
Order By: Relevance
“…This was still much higher than commonly estimated reliabilities of anchoring tasks (for an overview, see Röseler et al, 2019, p. 21). Our expectation was that, despite the high power, we would not find a significant difference between the reliability reported by Frech et al (2020) and the reliability in the present study, and thus, we would be able to conclude that the number of adjustment steps is indeed a reliable anchoring parameter.…”
Section: Hypothesis On the Reliability Of Anchoringcontrasting
confidence: 57%
See 4 more Smart Citations
“…This was still much higher than commonly estimated reliabilities of anchoring tasks (for an overview, see Röseler et al, 2019, p. 21). Our expectation was that, despite the high power, we would not find a significant difference between the reliability reported by Frech et al (2020) and the reliability in the present study, and thus, we would be able to conclude that the number of adjustment steps is indeed a reliable anchoring parameter.…”
Section: Hypothesis On the Reliability Of Anchoringcontrasting
confidence: 57%
“…Hypothetical Adjustment Functions from a High Anchor for Two Subjects A and B Individual TOTE parameters have already been measured. Frech et al (2020) introduced a paradigm that required participants to indicate the adjustment steps they made. We used their data (https://osf.io/dq48j/, Study 2) to compute the reliabilities of different parameters and found that the total adjustment (α = .513, three items, N = 146) and the number of steps (α = .693) were reliable, but the average step size (α = .097) was not.…”
Section: Insufficient Adjustment Modelmentioning
confidence: 99%
See 3 more Smart Citations